Canopy Nitrogen Addition and Soil Warming Affect Conifer Seedlings’ Phenology but Have Limited Impact on Growth and Soil N Mineralization in Boreal Forests of Eastern Canada - Marty, Charles; Piquette, Joanie; Dussault-Chouinard, Émilie; Morin, Hubert; Thiffault, Nelson; Houle, Daniel; Bradley, Robert L.; Ouimet, Rock; Simpson, Myrna J.; Paré, Maxime C. (Frontiers in Forests and Global Change, 2020)
The increase in soil organic matter mineralization rate in boreal forests that may result from global warming is a major concern as it could release large amounts of C to the atmosphere. On the other hand, this may also release N to the soil and stimulate tree growth, which could partly offset the C losses from the soil. The long-term interaction between increased N deposition and soil warming on soil organic N mineralization and tree growth is still uncertain in the boreal zone. In this study, soil temperature was increased by +2–4°C from April to July with heating cables for a period of 9 years and N was applied above the canopy of mature stands from June to September for 7–9 years in two eastern Canada boreal forests [Bernatchez (BER) and Simoncouche (SIM)]. We assessed the effects of these treatments on organic N mineralization rate and on the growth, phenology and foliar N of Abies balsamea (L.) Mill. (balsam fir; BF) and Picea mariana (Mill.) BSP (black spruce; BS) seedlings. The soil warming (SW) treatment had no significant effect on N mineralization rates, whereas canopy N addition (CNA) decreased gross N mineralization rate by 23% and forest floor’s alkyl/O-alkyl C ratio by ∼15% relative to unfertilized plots. Foliar δ15N in the control plots was markedly lower in BS than in BF and at BER than at SIM (–4.8 and –2.9‰ in BS at BER and SIM, respectively; 1.6 and 3.8‰ in BF at BER and SIM, respectively) likely due to a higher contribution of 15N-depleted N derived from mycorrhizal fungi in BS and at BER, the colder and the more N-depleted site. The treatments had non-significant effects on seedling growth and foliar chemistry but SW caused a premature bud outbreak and faster bud development for both species at both sites. Overall, our results show that increased soil temperature and N deposition in boreal forests may not impact soil fertility and vegetation growth as much as previously thought, but climate warming, by initiating earlier and faster bud development, may however expose seedlings to late spring frosts in the future.